Environmental sustainability through green HRM: Measuring the perception of university managers - Lashari, Ishfaque Ahmed; Li, Qiyuan; Maitlo, Qamaruddin; Bughio, Faraz Ali; Jhatial, Ashique Ali; Rashidi Syed, Obed (Frontiers in Psychology, 2022)
Environmental sustainability has gained great momentum worldwide especially in the United Nations (UN), governments, and corporations, and by those who promote global awareness of environmental challenges and are engaged in environmental management. Even as these stakeholders struggle hard, academia has actively engaged in an ongoing debate to make “green human resource management” an independent field of research and teaching. From the large body of academic literature, it has been observed that the field is yet in its embryonic stage in many developing countries such as Pakistan and there is insufficient knowledge on how universities face and manage environmental challenges. Hence, this study addressed this gap in the literature and measured the perception of public and private sector university managers regarding environmental sustainability by using a multi-respondent multi-wave design and collected data from academic heads/supervisors and university faculty in three-time intervals. The data found support for all the hypothetical relationships. The study revealed that the green human resource management (GHRM) practices of public and private universities have a positive impact on environmental sustainability through the mediation of innovative work behavior of employees.